Sosialisasi Istilah Bidang Teknologi dalam Bahasa Indonesia Baku dan Penerapannya di Ruang Publik - Faridatun Nida (Politeknik Negeri Cilacap, 2021)
Technological development leads to the creation of technological terms. The terms are dominantly created in English language. It affects the non-English technology-user. Many users are from Indonesia. In its usage, English terms are mixed with Indonesian. The mixture of language is indicated to interfere the Indonesian language users. In order to preserve the purity of Indonesian language, equivalent words to those technology terms are given. Nevertheless, the equivalent has not been optimally applied. Hence, there is a need for conducting community service activities entitle Sosialisasi Istilah Bidang Teknologi dalam Bahasa Indonesia Baku dan Penerapannya di Ruang Publik. The participants are students of Universitas Amikom Purwokerto. The activities are aimed to give the participants knowledge and motivation to use Indonesian technology terms as produced with the reference of English technology terms. Furthermore, there is also introduction about Seranai Padanan Asing Indonesia, one of the features that can be found in the web of Badan Pengembangan dan Pembinaan Bahasa, Ministry of Education and Culture, Republic of Indonesia. Students in higher education are regarded as a part of society that is expected to apply Indonesian equivalent terms of technology, at least in writing thesis or another formal academic text. They can utilize SPAI for finding the equivalent. By applying the Indonesian terms, they directly support the preservation of Indonesian languageTechnological development leads to the creation of technological terms. The terms are dominantly created in English language. It affects the non-English technology-user. Many users are from Indonesia. In its usage, English terms are mixed with Indonesian. The mixture of language is indicated to interfere the Indonesian language users. In order to preserve the purity of Indonesian language, equivalent words to those technology terms are given. Nevertheless, the equivalent has not been optimally applied. Hence, there is a need for conducting community service activities entitle Sosialisasi Istilah Bidang Teknologi dalam Bahasa Indonesia Baku dan Penerapannya di Ruang Publik. The participants are students of Universitas Amikom Purwokerto. The activities are aimed to give the participants knowledge and motivation to use Indonesian technology terms as produced with the reference of English technology terms. Furthermore, there is also introduction about Seranai Padanan Asing Indonesia, one of the features that can be found in the web of Badan Pengembangan dan Pembinaan Bahasa, Ministry of Education and Culture, Republic of Indonesia. Students in higher education are regarded as a part of society that is expected to apply Indonesian equivalent terms of technology, at least in writing thesis or another formal academic text. They can utilize SPAI for finding the equivalent. By applying the Indonesian terms, they directly support the preservation of Indonesian language